Microbial biomass, basal respiration, and microbial indices of soil in diverse croplands in a region of northwestern Turkey (Bartin) - Bolat, İlyas; Bolat, İlyas (Springer, 2019)
Legumes are very important both ecologically and agriculturally, as well as economically since soil quality can be improved by the added nitrogen and increased organic matter content they provide. It can be advantageous to apply quantitative methods to indicate soil quality using a dataset of soil characteristics that includes microbial biomass content and activity. The Western Black Sea Region of Turkey was chosen as the study area with the aim of determining the variations in the soil characteristics (physical, chemical, and microbiological) in diverse croplands. At the sites sampled, marked differences were found in the bulk density, clay, soil temperature, soil moisture content, organic carbon, total N, C-org/N-total ratio, and microbial characteristics of vetch (Vicia sativa L.), alfalfa (Medicago sativa L.), and sainfoin (Onobrychis sativa L.) croplands. There was a significant increase (P < 0.05) in the microbial biomass carbon content in the alfalfa (709.27 mu g g(-1)) and sainfoin (607.22 mu g g(-1)) croplands compared with the vetch (558.07 mu g g(-1)) cropland. Microbial biomass nitrogen was significantly lower in the vetch (103.67 mu g g(-1)) cropland compared with that in the sainfoin (127.42 mu g g(-1)) and alfalfa (140.26 mu g g(-1)). The highest basal respiration was determined in the alfalfa (1.09 mu g CO2-C g(-1) soil h(-1)) cropland, while the lowest was found in the vetch (0.54 mu g CO2-C g(-1) soil h(-1)) cropland. The mean C-mic/C-org percentage of the soils was lower in the sainfoin cropland when compared with the other croplands; however, statistically, no difference (P > 0.05) was observed among them. The soil under Onobrychis sativa L. and Vicia sativa L. exhibited the highest (1.67 mg CO2-C g(-1) C-mic h(-1)) and lowest (1.03 mg CO2-C g(-1) C-mic h(-1)) mean metabolic quotients (qCO(2)), respectively. When the microbial biomass carbon and nitrogen were taken into account, the high qCO(2) values may have been an indication that the microbial biomass of decomposed organic compounds was more active, rather than signifying a result of metabolic stress. Consequently, it can be said that the variations found in the metabolic quotient, basal respiration, and microbial biomass among the different croplands were related to changes inmicrobial activity. Furthermore, the physical, chemical, and microbiological results indicated that the soils of Medicago sativa L. and Onobrychis sativa L. were of higher quality than the Vicia sativa L. soil.
Keywords: Alfalfa; Legumes; Microbial Indicators; Onobrychis Sativa L.; Organic C; Soil; Vicia Sativa L.